DEVELOPMENT OF SPEAKING SKILL ASSESSMENT INSTRUMENTS ON LEARNING INDONESIAN LANGUAGE ANDROID-BASED AT PRIMARY SCHOOL - Farida, Haning; Haryono, Haryono; Lestari, Wahyu (Educational Management, 2020)
Assassement instruments of speaking skills used by teacher, not yet to able to describe students speaking skills. The teacher was also found to have no assessement rubrics. This developmental research aimed to produce teacher?s handbook in the form of valid, reliable, effective, and practical android based-student speaking skill assessment on learning Indonesian language at primary school. This research referred to Borg & Gall with 10 stages of development. However, this research only used until the ninth step. The findings showed that (1) based on expert judgment, the instrument was worthy to test with some revision, (2) empirical reliability of those four instruments both in small and large test scales was reliable, (3) the instrument construct validity was analyzed by Confirmatory Factor Analysis (CFA), all of the constructs were valid, (4) the developed product an android based student speaking skill instrument development was valid, reliable, and practical. The judgment based on the homeclass teacher showed that the product was practice to assess student speaking skill.